Teachers’ Perception towards the use of Problem-Based Learning for Teaching and Learning of Mathematics in Lagos State Secondary Schools - Kasumu Abayomi Adeoye; Kasumu Rebecca Oluwayimika (Journal of Learning and Educational Policy, 2023)
In a method called issue-based learning, students learn about a subject by collaborating in groups to find a solution to an unrestricted problem. The motivation and learning are driven by this issue. The study is a descriptive survey that aims to find out how teachers in secondary schools in Lagos State feel about using problem-based learning to teach and learn mathematics. The study was conducted at Corona Secondary School in Lekki and St. Saviours High School in Ikotun, both in Lagos State, Nigeria. 247 instructors from Corona Secondary School and 205 from St. Saviours High School in Lagos State, Nigeria, make up the study’s population. 100 instructors from the two schools in Lagos state were the study’s sample. 100 teachers were part of the study’s sample. Candidates were picked through a stratified sampling process. The instrument used for the study is a standardized 30-item questionnaire called Teachers Perspective towards the use of Problem-Based Learning for Teaching and Learning of Mathematics in Lagos State Secondary Schools (TPTPBLTLMLSSS). The study used both face validity and content validity. Pearson product moment correlation was used to generate reliability co-efficient of 0.72. The statistical methods employed for the study were mean and z test.